2011
DOI: 10.1016/j.bone.2010.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of bone development and homeostasis by trisomy in Ts65Dn Down syndrome mice

Abstract: Down syndrome (DS) is a genetic disorder resulting from trisomy 21 that causes cognitive impairment, low muscle tone and craniofacial alterations. Morphometric studies of the craniofacial and appendicular skeleton in individuals with DS suggest that bone development and homeostasis are affected by trisomy. The Ts65Dn mouse model has three copies of approximately half the genes found on human chromosome 21 and exhibits craniofacial skeletal and size differences similar to those observed in humans with DS. We hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
47
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 44 publications
8
47
3
Order By: Relevance
“…For skeletal parameters in DS mouse models, we and others have identified significant deficits in BMD, trabecular bone parameters (thickness, separation and number) and cortical bone measures in Ts65Dn mice compared to euploid control mice [17]. Significant deficits in mineral apposition rate (MAR), bone formation rate (BFR), and strength properties in trisomic mice compared to controls were also observed [17, 26, 27]. …”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…For skeletal parameters in DS mouse models, we and others have identified significant deficits in BMD, trabecular bone parameters (thickness, separation and number) and cortical bone measures in Ts65Dn mice compared to euploid control mice [17]. Significant deficits in mineral apposition rate (MAR), bone formation rate (BFR), and strength properties in trisomic mice compared to controls were also observed [17, 26, 27]. …”
Section: Introductionmentioning
confidence: 96%
“…The Ts(17 16 )65Dn (Ts65Dn) mouse model is the most extensively studied and widely used animal model of DS and captures several behavioral and skeletal defects that are seen in humans with DS [13, 1720]. We and others have shown that Ts65Dn mice exhibit behavioral and functional neurological deficits, including a variety of deficits on learning and memory tasks [20, 21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, deficiencies in bone formation [Parsons et al, 2007; Blazek et al, 2011]; brachycephaly, reduced facial, and cranial vault dimensions [Richtsmeier et al, 2000, 2002; Hill et al, 2007], and reduced cerebellar volume and granule cell density [Baxter et al, 2000] have been found in humans with DS and in Ts65Dn mice. Additionally, effects on hippocampal-based behaviors [Reeves et al, 1995; Pennington et al, 2003], occurrence of hematopoietic disease in the presence of GATA1 mutations [Crispino, 2005], and many similar effects on gene expression levels [Gardiner et al, 2003] have been discovered in people with DS and in Ts65Dn mice.…”
Section: Introductionmentioning
confidence: 99%
“…These same cells are then responsible for the maintenance of the skeleton during adulthood and aging [12]. The measurement of bone biochemical markers provides a path to understand the underlying bone physiology, yet such information is scarce in patients with DS [13]. …”
Section: Introductionmentioning
confidence: 99%